Cognitive and Simulation Modeling of Regional Economic System Development - Larisa A. Ginis; Galina V. Gorelova; Anna E. Kolodenkova (International Journal of Economics and Financial Issues, 2016)
Sustainable development of regional economy is the declared as a strategic objective of the state. From these positions, studying of the regional socio-economic phenomena and processes, development of the corresponding research and managerial tools are actual tasks. Authors consider the regional economy as a complex hierarchical system. This requires identification of its state, structure, particularities in its development and governance. These factors are investigated using the means of simulation modeling. Authors suggest to use the developed cognitive and simulation modeling methodology, which is based on cognitive approach, the theory of hierarchical multilevel structures, fixed and fuzzy directed graphs. The study illustrates possibilities of cognitive-simulation modeling and foresight of the socio-economic system development at the regional level.